A formação da paisagem em Dinâmica Subtil, de António Ramos Rosa - Terreri, Grida Auyra Pignata (2015)
Michel Collot, scholar of the new Cultural Geography, proposes us that the literary landscape is a landscape built and, concurrently, a landscape in construction, both passing through the individual. Thus, this work aims to analyze the poetic work in Dinâmica Subtil of António Ramos Rosa, through the Theory of Landscape, demonstrating how the literary landscape shows itself in the work and through witch resources it opens space for the construction of the literary landscape by the reader; this way, it aims to demonstrate how the literary landscape given in Dinâmica Subtil is formed and how can it be transformed by the reader.